A supremacia (in)constitucional dos poderes do Presidente da República e a teoria da separação dos poderes - Carvalho, Jeferson Moreira de (2005)
The purpose of the following thesis is to show that even the Federal Constitution had adopted the Theory of power s division, as according to the idea of Montesquieu, foreseeing the existence of the Executive, Legislative and Judiciary, independents and harmonics, although with an certain control of each other to prevent the concentration of powers in only one person or only one organ, in fact the Constitution itself by preventing the power of the President allows him that he interferes on others powers, therefore, puts him in supremacy related to the Legislative and to the Judiciary. The study in front of the history in Brazil justifies itself, where is noted the President, using the constitutionals powers that are given to him, legislates more than the Legislative name members to the Audit Court, which is Legislative´s aid organ with the function of inspect the President s accounts. What is respected to the Judiciary, the history shows the nomination of integrants of the Courts, who are derived from political parties, fact that is not accepted by the Judiciary that members have compromises with ideologies from a political party. Therefore, the creation of an organ with outer control of the Judiciary, puts him in a lower position in relation to the others powers, which not suffer this kind of control, once more recognizing the interference of the President that name the members of the outer control. Withdraw the presidential is not impose, also this form of government do not allow the absolutism presidential. Basing on Montesquieu´s theory and reading the Constitution there is the conclusion of the necessity in modifications on the Constitutional Text in order to repel the supremacy of powers from the president and locate the Three Powers of the State on the same constitutional level, considering that the experience and the history show that the real and alive forces of powers that constitutes the Brazilian State do not accept the concentration of powers in only one person or only one organism